Pengaruh Implementasi Quality Management System (Qms) Dan Layout Mesin Terhadap Kualitas Produksi Kemasan Botol Minum Dengan Penerapan Good Manufacturing Practice (Gmp) Sebagai Variabel Moderasi Pada PT. Diamond - Andrew Kellyen; Ari Soeti Yani (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2022)
This study aims to determine the effect of the implementation of a quality management system (QMS) and machine layout on the quality of drinking bottle packaging production with the application of good manufacturing practice (GMP) as a moderating variable at PT. Diamonds. The results showed that the implementation of the Quality Management System (QMS) had a significant and positive effect on the quality of plastic bottle packaging production. Machine Layout has a significant and positive effect on the production of plastic bottle packaging. The Good Manufacturing Practices (GMP) system has a significant and positive effect on the production of plastic bottle packaging. The Good Manufacturing Practices (GMP) system has an insignificant and positive effect and is unable to moderate the implementation of the Quality Management System (QMS) on the production of plastic bottle packaging. System Good Manufacturing Practices (GMP) has a negative insignificant effect, unable to moderate Machine Layout on the production of plastic bottle packaging Keywords: Quality Management System (QMS), Machine Layout, Production Quality, Good Manufacturing Practice (GMP)